2020
DOI: 10.5194/amt-13-2547-2020
|View full text |Cite
|
Sign up to set email alerts
|

Consistency and structural uncertainty of multi-mission GPS radio occultation records

Abstract: Abstract. Atmospheric climate monitoring requires observations of high quality that conform to the criteria of the Global Climate Observing System (GCOS). Radio occultation (RO) data based on Global Positioning System (GPS) signals are available since 2001 from several satellite missions with global coverage, high accuracy, and high vertical resolution in the troposphere and lower stratosphere. We assess the consistency and long-term stability of multi-satellite RO observations for use as climate data records.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 104 publications
2
52
0
Order By: Relevance
“…The data quality of these RO missions (except for COSMIC-2), including precision, stability, and structural uncertainty owing to inversion implementations, has been intensively validated in previous studies (i.e., [30][31][32]). All the RO data, including COSMIC-2 data, are downloaded from UCAR CDAAC (http://cosmic.cosmic.ucar.edu/cdaac/index.html).…”
Section: Ro Data From Cosmic Kompsat 5 and Metop-a-b -C Gras Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The data quality of these RO missions (except for COSMIC-2), including precision, stability, and structural uncertainty owing to inversion implementations, has been intensively validated in previous studies (i.e., [30][31][32]). All the RO data, including COSMIC-2 data, are downloaded from UCAR CDAAC (http://cosmic.cosmic.ucar.edu/cdaac/index.html).…”
Section: Ro Data From Cosmic Kompsat 5 and Metop-a-b -C Gras Andmentioning
confidence: 99%
“…The upper troposphere and lower stratosphere (UT/LS) is a critical region for understanding the radiative balance and climate processes. Studies have demonstrated that COSMIC temperature profiles in the lower stratosphere are very accurate (+/− 0.1K comparing with RS92 [46]) and stable (with a structural uncertainty of +/− 0.3 K in the trend [31]).…”
Section: Accuracy and Uncertainty Of Cosmic-2 Temperature In The Lowementioning
confidence: 99%
“…6b). Recent studies using meridional winds and the Hilbert transform have shown the benefits of refining the methodology with semi-geostrophic coordinate adjustment Wirth, 2015, 2017) and even using wave activity flux (Takaya and Nakamura, 2001) for RWP diagnostics and optimizing the envelope's shape. Our approach to describe the phase and envelope propagation of an RWP in Fig.…”
Section: Classical Rwp Examplementioning
confidence: 99%
“…With the advent of the RO, the scientific community was able to better understand the TC inner thermal structure and water vapour (WV) content at different layers. The TC track and intensity predictions, until 2006, were almost completely based on parameters such as surface temperature, cloud top temperature and surface winds at the outer radius (Brueske and Velden, 2003;Demuth et al, 2004;Dvorak, 1975;Kidder et al, 1978;Velden et al, 2006) from different remote sensing techniques such as infrared and microwave sounders and imagers (King et al, 1992), lidar (Poole et al, 2003), reflected light polarization (Knibbe et al, 2000), and oxygen A-band technique (Koelemeijer et al, 2002). Anthes et al (2003) were the first, comparing RO soundings with radiosonde observations during the Typhoon Toraji in 2001.…”
Section: Introductionmentioning
confidence: 99%